Therapie des subakromialen Schmerzsyndroms - Matthijs, Anja (VPT Magazin, 2019)
Im VPTMAGAZIN stellen wir regelmäßig aktuelle Studienergebnisse vor. Diesmal: Chaconas EJ, Kolber MJ, Hanney WJ, Daugherty ML, Wilson SH, Sheets C. Shoulder external rotator eccentric training versus general shoulder exercise for subacromial pain syndrome: a randomized controlled trial. Int J Sports Phys Ther. 2017;12:1121–133.